Combination Cockle Shells (Anadara granosa) and Calcite Lime to Improve Swamp Water pH for Catfish (Pangasius sp.) Culture - Dade Jubaedah; Marsi Marsi; Marini Wijayanti; Sofiatul Rahmani (Journal Omni-Akuatika, 2020)
Cockle shells was proven potential used as an alternative liming material. Combination of lime derived from cockle shells with calcite as common lime materials used to overcome limited quantity of cockle shells as the problem of seasonal availability of cockle shells. Besides, these materials have difference characteristics that to be expected can give better effect to pH of soil and water. This study aims to determine the best combination dose between cockle shell limes and calcite to increase the pH of water and soil, survival rate and growth of catfish (Pangasius sp.). The study used completely randomized design (CRD) with 5 treatments and 3 replications. The treatment of different combination of lime doses 100% calcite (P1), 100% cockle shell limes (P2), 75% calciteand 25% cockle shell limes (P3), 50% calcite and 50% cockle shell limes (P4), and 25% calcite and 75% cockle shell limes (P5), dose of lime used as much as 7,000 kg/ha CaO equivalent. The result showed that P4 was the best treatment according to data of swamp water pH was 8.13 and soil pH was 8.07 at final day (day 60), alkalinity 153.33 mg.L-1 CaCO3 equivalent, Ca 104.15 mg.L-1,100% survival rate, 11.23 cm absolute growth of length, 38.60 g absolute growth of weight and 128.38% feed efficiency.